Lewy bodies are immunoreactive with antibodies raised to gelsolin related amyloid-Finnish type. - Wisniewski, T. (1991)
Lewy bodies (LB) are intraneuronal, cytoplasmic inclusion bodies. They are invariably present in Parkinson's and diffuse LB diseases. Their composition by direct biochemical methods is unknown, although LBs are immunoreactive with a number of antibodies, including anti-ubiquitin and anti-neurofilament antibodies. Familial amyloidosis, Finnish type (FAF), is an autosomal-dominant form of systemic amyloidosis. The authors have isolated and partially sequenced the amyloid. The protein has significant sequence identity with gelsolin, an actin-modulating protein. Rabbit polyclonal antibodies raised to the FAF amyloid not only immunostain the amyloid but also LBs in the cortex and substantia nigra of Parkinson's and diffuse LB disease brains. Immunoreactivity is absorbed by the purified amyloid but is unaffected by ubiquitin. This provides a link between the LB and one of the human amyloidoses, FAF.